Sharing of biological effect and receptors between guinea pig insulin and platelet-derived growth factor. - King, G L (1983)
Insulins from the hystricomorphs (guinea pig, porcupine, coypu, and casiragua) at high concentration stimulate DNA synthesis in human fibroblasts to a greater level than other mammalian insulins or insulin-like growth factors (IGFs). 125I-Labeled guinea pig insulin binds to a specific receptor and this binding is competed for by hystricomorph insulins but not by porcine insulin or IGFs. Fetal bovine serum also inhibits the binding of 125I-labeled guinea pig insulin and is more potent than fetal bovine plasma, in concordance with their relative potencies for growth stimulation in human fibroblasts. Of several other known growth factors tested, only platelet-derived growth factor (PDGF) inhibits binding of 125I-labeled guinea pig insulin. Four preparations of PDGF that vary in purity and potency for the stimulation of DNA synthesis in human fibroblasts over a 1,000-fold range compete with binding of 125I-labeled guinea pig insulin in proportion to their biological potencies. The purest preparation of PDGF is able to inhibit binding of 125I-labeled guinea pig insulin by 50% at 15 ng/ml (0.25 nM). Biologically, guinea pig insulin, like PDGF, exhibits a synergistic effect with plasma in initiating DNA synthesis in human fibroblasts; this effect is not observed with other mammalian insulins or IGFs. Thus, hystricomorph insulins appear to be mediating their growth-promoting effect through a different receptor and mechanism than other mammalian insulins or IGFs. Further, hystricomorph insulins may be sharing the mechanism of action for their growth effects with PDGF, perhaps suggesting some relationship between these peptides from very different sources.